The role of blood–brain barrier dysfunction in cognitive impairments in bipolar disorder—a narrative review - Millett, Caitlin E.; Monir, Faria; Sanelli, Pina (Frontiers in Human Neuroscience, 2025)
Bipolar disorder (BD) is a chronic and debilitating mental illness affecting approximately 40 million people worldwide. Cognitive impairment is a core feature of BD, impacting daily functioning and persisting even during mood stability. Cognitive deficits are among the most reliable indicators of long-term functional outcomes in BD. Despite their significance, there are currently no widely available treatments targeting cognitive impairment in BD, largely due to our limited understanding of the underlying pathophysiology. A healthy blood–brain barrier (BBB) is essential for brain homeostasis, serving as a protective filter that restricts peripheral toxins, pathogens, and ions from entering the brain and disrupting neuronal function. Increased BBB permeability can allow harmful substances to infiltrate the brain, potentially leading to neuroinflammation, disrupted signaling, and damage to brain tissue, all of which may contribute to cognitive impairments in BD. Thus, BBB dysfunction could represent an upstream driver of cognitive impairment in BD, offering a potential target for disease-modifying interventions. This narrative review examined the evidence for the link between BBB permeability and cognitive deficits in BD. Our search yielded limited studies with mixed findings, highlighting the significant need for further research to explore this critical area and its potential for developing disease-modifying treatments.